SANKSI PIDANA TERHADAP OKNUM APARAT PENEGAK HUKUM PELANGGAR UNDANG UNDANG NARKOTIKA - Komaria, Nina; Permana, Yana Sukma (Neolectura, 2025)
Narcotics trafficking has developed into a threat that has penetrated various levels of society throughout the world. Even though efforts have been made to eradicate narcotics abuse, the narcotics distribution network is increasingly complex and difficult to stop. This phenomenon places significant pressure on law enforcement officers in police institutions to stop drug trafficking. The police institution is at the forefront in combating the distribution and abuse of narcotics. However, this noble task is being undermined by several law enforcement officers who are involved in committing criminal acts of narcotics abuse. This journal research takes a case study of the Republic of Indonesia Supreme Court Cassation Decision No. 4711 K/Pid.Sus/2020 dated 16 December 2020 which highlights the problem formulation and objectives to find out how the law regulates narcotics crimes and how criminal law is applied to individual law enforcement officers who violate the narcotics law. The method used is a normative writing method using secondary legal material sources obtained through document analysis, and legal material using legal argumentation. The research results show that the legal regulation of narcotics crimes is regulated in Law No. 35 of 2009 concerning Narcotics, which is applied to all levels of society who violate narcotics, including law enforcement officers who violate narcotics laws.